Implementation of Multi-representation Learning on Climate Change Integrated Dynamic Fluid to Improve Student’s Problem-Solving Skills - Erina Krisnaningsih; Eko Hariyono (Berkala Ilmiah Pendidikan Fisika, 2022)
This research aims to analyze the implementation of multi-representation learning on climate change topics integrated fluid dynamics to improve students' problem-solving skills and analyze student responses to multi-representation learning on climate change topics integrated fluid dynamics. The type of this research is quantitative research with a pre-experimental that uses a one-group pretest-posttest design. This research was conducted in XI MIPA-1 at Senior High School 4 Sidoarjo with 36 students. Data collection techniques in this research used tests with test instruments in the form of description questions and questionnaires (responses) on a Likert scale. The data analysis technique is N-gain for the description test instrument and descriptive for student response questionnaires. The results of this research obtained the score of N-gain is 0.565 with a category of the medium. The results of student responses carried out using a Likert scale questionnaire for ten statements had positive and very positive results with a percentage of more than 77%. Thus, it was concluded that learning multi-representation could improve students' problem-solving skills with the topic of climate change integrated with fluid dynamics and elicit positive and very positive responses from students.